Genotype-Phenotype Associations in Patients With Type-1, Type-2, and Atypical NF1 Microdeletions - Büki, Gergely; Zsigmond, Anna; Czakó, Márta; Szalai, Renáta; Antal, Gréta; Farkas, Viktor; Fekete, György; Nagy, Dóra; Széll, Márta; Tihanyi, Marianna; Melegh, Béla; Hadzsiev, Kinga; et al. (Frontiers in Genetics, 2021)
Neurofibromatosis type 1 is a tumour predisposition syndrome inherited in autosomal dominant manner. Besides the intragenic loss-of-function mutations in NF1 gene, large deletions encompassing the NF1 gene and its flanking regions are responsible for the development of the variable clinical phenotype. These large deletions titled as NF1 microdeletions lead to a more severe clinical phenotype than those observed in patients with intragenic NF1 mutations. Around 5-10% of the cases harbour large deletion and four major types of NF1 microdeletions (type 1, 2, 3 and atypical) have been identified so far. They are distinguishable in term of their size and the location of the breakpoints, by the frequency of somatic mosaicism with normal cells not harbouring the deletion and by the number of the affected genes within the deleted region. In our study genotype-phenotype analyses have been performed in 17 mostly pediatric patients with NF1 microdeletion syndrome identified by multiplex ligation-dependent probe amplification after systematic sequencing of the NF1 gene. Confirmation and classification of the NF1 large deletions were performed using array comparative genomic hybridization, where it was feasible. In our patient cohort 70% of the patients possess type-1 deletion, one patient harbours type-2 deletion and 23% of our cases have atypical NF1 deletion. All the atypical deletions identified in this study proved to be novel. One patient with atypical deletion displayed mosaicism. In our study NF1 microdeletion patients presented dysmorphic facial features, macrocephaly, large hands and feet, delayed cognitive development and/or learning difficulties, speech difficulties, overgrowth more often than patients with intragenic NF1 mutations. Moreover, neurobehavior problems, macrocephaly and overgrowth were less frequent in atypical cases compared to type-1 deletion. Proper diagnosis is challenging in certain patients since several clinical manifestations show age-dependency. Large tumour load exhibited more frequently in this type of disorder, therefore better understanding of genotype-phenotype correlations and progress of the disease is essential for individuals suffering from neurofibromatosis to improve the quality of their life. Our study presented additional clinical data related to NF1 microdeletion patients especially for pediatric cases and it contributes to the better understanding of this type of disorder.